1991
DOI: 10.1139/x91-137
|View full text |Cite
|
Sign up to set email alerts
|

Aseptic tapping of sugar maple (Acersaccharum) results in light color grade syrup

Abstract: An aseptic technique was used to collect 227 sap samples from 84 tapholes, including several initial and successive collections, of 27 sugar maples (Acersaccharum Marsh.) over six sap flow seasons (mid-February to late April). In this technique, all material used is sterilized, and the bark as well is sterilized with alcohol. Of the 227 sap samples, 62.5% were sterile or essentially sterile (0–10 colony forming units of microorganisms per millilitre), and of the 74 sap samples from initial collections, 83.8% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Results obtained emphasize the need to elaborate strategies to control microbial contamination of the taphole, since this contamination will serve as inoculum for the sap collection and holding system. Research in the past has demonstrated that microorganisms can adversely affect the quality of maple syrup (5,15,18,21). This quality is primarily based on the color, flavor, and texture of maple syrup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results obtained emphasize the need to elaborate strategies to control microbial contamination of the taphole, since this contamination will serve as inoculum for the sap collection and holding system. Research in the past has demonstrated that microorganisms can adversely affect the quality of maple syrup (5,15,18,21). This quality is primarily based on the color, flavor, and texture of maple syrup.…”
Section: Discussionmentioning
confidence: 99%
“…The sap is a solution containing between 1 and 5.4% solids composed of different organic compounds, such as sucrose, glucose, fructose, organic acids, and nitrogenous and phenolic compounds, as well as different minerals (19). This solution is known to be a good nutrient medium for microorganisms, and their growth in the sap will eventually affect the quality of maple syrup and other end products (15,18,21). These microorganisms can enter the sap, notably by unsanitary tapping, since the taphole constitutes their first point of entry into maple sap.…”
mentioning
confidence: 99%
“…Research in this field has already demonstrated that the sanitary quality of maple sap has an effect on the physicochemical and sensory quality of maple syrup (Edson 1912). Some of these effects are undesirable and result in syrups that are dark in color (Morselli and Whalen 1991), present off-flavors or have a "ropy" texture (Fabian and Buskirk 1935;Holgate 1950). The microorganisms in maple sap play a role in the enzymatic hydrolysis of sucrose-producing reducing sugars (glucose and fructose), and these sugars are responsible for the dark color and the intense caramel flavor that arise during evaporation, masking the characteristic maple flavor of syrup (Naghski and Willits 1957).…”
Section: Aple Syrup Is Obtained By Using Heat To Evaporate Maplementioning
confidence: 99%
“…Table 1 shows the evolution during the tapping season of the respective types of microbial contamination. Since maple sap is sterile in the xylem of maple trees (Morselli and Whalen 1991), it follows that these microorganisms must be introduced into the sap after tapping through unsanitary tapping procedures and/or the contaminated surfaces of collection tubes, reverse osmosis Figure 3Number of sap samples found for each sap contamination class according to the invert sugar content systems, and storage tanks. This contamination depends on time and weather conditions.…”
Section: Atp Versus Microbial Countsmentioning
confidence: 99%
“…Unlike honey, that gets much of its character from the floral species in surrounding fields (Corbella and Cozzolino, 2005), maple syrup quality is influenced by the timing of sap harvest. Early season syrups tend to be light-colored, while late season batches are much darker, with a more robust taste (Morselli and Whalen, 1991). Optical spectroscopy is of interest not only for routine physico-chemical testing, but also to highlight characteristics 0260-8774/$ -see front matter Ó 2009 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%